2006
DOI: 10.1002/cncr.22312
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neutral endopeptidase and activation of protein kinase B (Akt) is associated with prostate cancer progression

Abstract: BACKGROUND. Neutral endopeptidase (NEP) is a cell‐surface peptidase that can regulate the activation of Akt kinase through catalytic‐dependent and independent mechanisms. NEP expression is absent in approximately 50% of prostate cancers. The authors investigated whether NEP loss in vivo would result in Akt phosphorylation and potentially contribute to prostate cancer progression by examining the interaction of NEP, Akt, and phosphatase and tensin homolog (PTEN) in a prostate xenograft model and in clinical spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
3
25
0
1
Order By: Relevance
“…CUR-Induced NEP Upregulation Suppresses the AKT/NF-κB Pathway in N2a/APPswe Cells NEP has been demonstrated as an inhibitor of AKT (11). To determine whether upregulation of NEP induced by CUR mediates downregulation of activation of AKT and its downstream target NF-κB, the N2a/APPswe cells, engineered to over-produce Aβ (30), was used.…”
Section: Cur Reverses Hypermethylated Cpg Sites Of Nep Gene In N2a/wtmentioning
confidence: 99%
See 2 more Smart Citations
“…CUR-Induced NEP Upregulation Suppresses the AKT/NF-κB Pathway in N2a/APPswe Cells NEP has been demonstrated as an inhibitor of AKT (11). To determine whether upregulation of NEP induced by CUR mediates downregulation of activation of AKT and its downstream target NF-κB, the N2a/APPswe cells, engineered to over-produce Aβ (30), was used.…”
Section: Cur Reverses Hypermethylated Cpg Sites Of Nep Gene In N2a/wtmentioning
confidence: 99%
“…Subsequent studies have demonstrated that the pro-inflammatory factor NF-κB activated by several molecules including AKT is involved in the inflammation progress of AD (7,8). Besides the property of Aβ clearance in AD brains, NEP has also been reported to have negative regulatory effect on AKT signaling (11). In this study, we confirmed the ability of CUR treatment to inhibit AKT/NF-κB signaling by suppressing the activation of AKT and NF-κB in N2a/APPswe cells in NEP-dependent way.…”
Section: Inhibition Of Akt/nf-κb Signaling By Cur Is Associated With mentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,8 Loss of NEP in vivo in primary prostate cancers correlates with increased Akt phosphorylation, and predicts biochemical relapse in patients who have undergone radical prostatectomy. 6,9 Together, these studies suggest that NEP loss contributes to prostate cancer progression.…”
Section: Introductionmentioning
confidence: 81%
“…Fewer studies have been performed to evaluate the benefit of inhibiting neutral endopeptidase, the major bradykinin-degrading enzyme in the heart [45,46]. A proangiogenic effect is indicated by studies reporting faster cancer progression to be associated with increased tumor vascularization under neutral endopeptidase inhibition [47,48]. Again, further studies in relevant models are necessary to understand the therapeutic potential for kininase blockers in vascularization of cardiovascular patients with and without diabetes.…”
Section: Nicolle Kränkel Phdmentioning
confidence: 99%